Correlation between knowledge level, side effect severity, family support, and antiretroviral therapy adherence in HIV/AIDS patients in Greater Malang, East Java, Indonesia - Ema Pristi Yunita; Rayfika Nokha Kusuma Wardani; Bambang Sidharta (Pensoft Publishers, 2023)
Human Immunodeficiency Virus (HIV) is a virus that attacks and weakens the human immune system, leading to Acquired Immune Deficiency Syndrome (AIDS) symptoms. East Java is one of the provinces in Indonesia with a high HIV prevalence. Antiretroviral therapy (ART) is a critical approach to slow down the growth rate of HIV since no medicine has been found for HIV/AIDS patients. Therefore, high adherence to ART is necessary to reduce viral replication and prevent the development of resistance. This study aimed to investigate the correlation between knowledge level, side effect severity, family support, and ART adherence in HIV/AIDS patients. This observational analytic study with a cross-sectional design was conducted in September-October 2022 at the Netral Plus Indonesia Foundation and Malang Islamic Hospital. The study included 55 HIV/AIDS patients, and the Spearman correlation test was used to analyze the data. There was no significant relationship between knowledge level, side effects, and adherence to ART treatment (p = 0.959; p = 0.719). However, family support was found to be significantly related to adherence to ART treatment (p = 0.004). The findings of this study suggest that family support is a crucial factor in the adherence to ART treatment among HIV/AIDS patients.